Factors Forming the Quality of Electronic Services of Payment System Service Providers (PJSP) QRIS on Micro Businesses (Merchants) in Bandung City with E-Service Quality and IS Success approaches - Ashila Dwiyanisa; Larashati, Irena; Annisa, Dhea Bunga (LPPM STMIK Mardira Indonesia, 2023)
Acceleration in various fields that occur today also affects the payment system that can be used by consumers. Consumers are currently presented with various cashless payment systems that are considered more convenient than previous payment methods. One of the cashless payment systems that are widely used today is QRIS or Quick Response Code Indonesian Standard. However, until now there has been no instrument that specifically measures the e-service quality provided by PJSP QRIS to its merchants. This research aims to provide alternative e-service quality with more specific indicators at PJSP QRIS for micro business merchants in Bandung City, with the E-Service Quality and IS Success approaches. In this study, the subjects observed were micro business merchants in Bandung City who used QRIS for their payment system. Respondents were determined based on non-probability sampling with a judgmental sampling technique of 190 respondents. This research uses quantitative methods with an exploratory factor analysis (EFA) approach to categorize and determine what factors make up the dimensions of electronic service quality. The research instrument used a questionnaire with 38 items that referred to the five dimensions of E-Service Quality and two dimensions of IS Success. Based on the research conducted, all the items studied formed three main factors that became measurements of QRIS e-service quality. The first is the responsiveness factor with 14 measurement items. The second is the assurance factor with five measurement items and the third factor is the reliability factor with 17 measurement items.